Credit risk management and effectiveness of credit activities: Evidence from Vietnam - Tien, Dat Pham; Nguyen, Kim Quoc Trung (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
The research aims to assess the effects of credit risk management on the effectiveness of credit activities at Vietnamese state-owned commercial banks. Based on the literature review and empirical studies, the aspects of credit risk management practices include four factors proposed in the research model, such as: credit terms, client appraisal, credit risk control, and collection policies. The author implements the descriptive statistical method and linear regression model on SPSS with data from a survey of credit officers from state-owned commercial banks in Vietnam. The findings show that credit term, client appraisal, and credit risk control positively influence loan performance at a 95% confidence interval. The paper also highlights the role of internal control as the mechanism for reducing credit risk and improving the effectiveness of credit activities.